2014
DOI: 10.1088/2043-6262/5/4/045006
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis, characterization of Au–Ag core–shell nanoparticles using gripe water and their applications in nonlinear optics and surface enhanced Raman studies

Abstract: In recent years there has been excessive progress in the 'green' chemistry approach for the synthesis of gold and silver nanoparticles. Bimetallic nanoparticles have gained special significance due to their unique tunable optical properties. Herein we report a facile one-pot, ecofriendly synthesis of Au-Ag bimetallic core-shell nanoparticles using gripe water as reducing as well as stabilizing agent. The as-synthesized Au-Ag nanoparticles are characterized using UV-Vis spectroscopy to determine the surface pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…This method was developed by Sheik-Bahae et al [36], to measure the sign and magnitude of nonlinear refraction n 2 of a material [37]. The beam from 532 nm Nd:YAG (CW) laser was focused using 3.5 cm lens.…”
Section: Nonlinear Optical Behaviour Of the Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was developed by Sheik-Bahae et al [36], to measure the sign and magnitude of nonlinear refraction n 2 of a material [37]. The beam from 532 nm Nd:YAG (CW) laser was focused using 3.5 cm lens.…”
Section: Nonlinear Optical Behaviour Of the Agnpsmentioning
confidence: 99%
“…inferred from the open aperture z-scan[37][38][39].The real and imaginary parts of the second order hyperpolarizability, γ, of the solutes were computed assuming additivity of the nonlinear contributions of the solvent and the solute and the applicability of the Lorentz local field approximation[40]. The optical nonlinear parameters are obtained from equations where is the nonlinear refractive index, k is the wave number (k=2π/λ) and ∆Φ 0 is the onaxis phase shift at the focus, I 0 is the peak intensity within the sample at the focus, L eff is the effective thickness of the sample (1 mm-quartz cuvette), S is the linear aperture transmittance (0.5) andis the normalized peak valley difference obtained from theclosed aperture z-scan trace, ∆T=1− , where is the normalized peak value from the open aperture plot [38-40].…”
mentioning
confidence: 99%
“…Venkateswarlu et al [39] reported two-step biosynthesized Fe 3 O 4 -Ag core/shell NPs (50 nm) using Vitis vinifera stem extract. Au-Ag core shell NPs (10 nm) were synthesized via one-pot method using grape water [40], a herbal medicinal drug. Plants seem to be the ideal candidates as they are suitable for expeditious large-scale green synthesis of core-shell NPs; the rate of synthesis being faster than those observed for processes aided by microorganisms [41].…”
Section: Greener Synthesis Of Core-shell Nanoparticles Using Plantsmentioning
confidence: 99%
“…Ag/Au (core/shell) nanoparticles were prepared using gripe water according to the procedure given in [15]. In a flask, 2 mL of 0.3 mM AgNO 3 was mixed with 10 mL of gripe water.…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%